CeO2 Encapsulated by Iron, Sulfur, and Nitrogen‐Doped Carbons for Enhanced Oxygen Reduction Reaction Catalytic Activity. Issue 3 (14th January 2020) - Ji, Mingjun; He, Bing; Yu, Yue; Yu, Xiaodan; Xing, Shuangxi
Abstract: The design and synthesis of highly stable, low‐cost electrocatalysts for the oxygen reduction reaction to supersede noble‐metal catalysts is critical for their application in the field of fuel cells. Herein, we report a facile approach for the synthesis of CeO2 encapsulated by iron, sulfur, and nitrogen‐doped carbon nanoparticles (CeO2 @Fe, S, N−C NPs) by pyrolyzing CeO2 @polypyrrole, which is obtained in the presence of sodium dodecylbenzene sulfonate as a surfactant and FeCl3 as an oxidant during the polymerization of pyrrole on the CeO2 surface. As Fe and S are effectively doped into the N‐doped carbon derived from polypyrrole, a large number of active sites are created, which greatly enhances the catalytic activity of the sample. The achieved sample displays excellent catalytic activity with an onset and halfwave potential of 0.924 V and 0.835 V, respectively, and a limiting current density of 5.45 mA cm −2 at the potential of 0.4 V vs. RHE. Moreover, it illustrates a high durability and strong methanol tolerance, endowing it with the prospect of applications in energy conversion. Abstract : Active cat . CeO2 encapsulated by iron, sulfur, nitrogen‐doped carbons display excellent oxygen reduction catalytic activity and are satisfactory stability.